ПРИОРИТЕТНЫЕ НАПРАВЛЕНИЯ ИНДУСТРИАЛЬНОГО РАЗВИТИЯ КАЗАХСТАНА - L. M. Bekenova (Экономика: стратегия и практика)
The purpose of this work is to analyze the industrial structure of the economy of Kazakhstan to identify the most promising areas of its development. In the course of the work, the main current state programs for industrial development, the main industrial indicators in dynamics, the structure of industrial production by types of economic activity, the main trends in industrial development, identified the most promising industries of Kazakhstan, identified problems and opportunities for their development, suggested possible solutions to problems.